Analysis of Workload of Medical Records Officers: Switching from Manual Medical Records to Electronic Medical Records in X Hospital in 2024: Workload of Medical Records Officers - Fitria Aryani Susanti (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2024)
After the Covid-19 pandemic at the beginning of 2020, transformations occurred in various fields, including health. The health sector is undergoing transformation, one of which is the birth of Minister of Health Regulation Number 24 of 2022 concerning Electronic Medical Records and Law Number 17 of 2023 concerning health. The research method used is descriptive research using qualitative and quantitative approaches. The research was conducted on 2-4 May 2024 at Hospital Electronic Medical Record activities only require 6 people; manual medical record activities consist of more than 18 activities, whereas for Electronic Medical Record activities only 8 activities are required; Time efficiency for manual medical record activities takes more than 86 hours with a fatigue factor of 8.6 hours, while for Electronic Medical Record activities it only takes 38 hours with a fatigue factor of 3.8 hours. The suggestion for optimize the transfer of manual medical record media to electronic medical records by upgrading existing Electronic Medical Records according to the needs of Hospital X and making a commitment with health workers and supporting staff to use Electronic Medical Records.